2022
DOI: 10.3389/fmicb.2022.973469
|View full text |Cite
|
Sign up to set email alerts
|

Diet drives the gut microbiome composition and assembly processes in winter migratory birds in the Poyang Lake wetland, China

Abstract: The complex gut bacterial communities may facilitate the function, distribution, and diversity of birds. For migratory birds, long-distance traveling poses selection pressures on their gut microbiota, ultimately affecting the birds’ health, fitness, ecology, and evolution. However, our understanding of mechanisms that underlie the assembly of the gut microbiome of migratory birds is limited. In this study, the gut microbiota of winter migratory birds in the Poyang Lake wetland was characterized using MiSeq seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…This is consistent with the results for gut bacteria in captive common and demoiselle cranes (Wang, 2022 ). Research has indicated that Firmicutes are more abundant in herbivorous animals (Wang et al, 2022 ), and their main function is to break down cellulose into volatile fatty acids that can be assimilated by the host, increase nutrient utilization, regulate T cells to strengthen host immunity, inhibit intestinal inflammation, and maintain the ecological balance of the gut microbiota (Fernando et al, 2010 ; Guan et al, 2017 ). The abundance of Firmicutes in the guts of common cranes was higher than that in demoiselle cranes, and this may be related to the different feeding habits of the two cranes.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the results for gut bacteria in captive common and demoiselle cranes (Wang, 2022 ). Research has indicated that Firmicutes are more abundant in herbivorous animals (Wang et al, 2022 ), and their main function is to break down cellulose into volatile fatty acids that can be assimilated by the host, increase nutrient utilization, regulate T cells to strengthen host immunity, inhibit intestinal inflammation, and maintain the ecological balance of the gut microbiota (Fernando et al, 2010 ; Guan et al, 2017 ). The abundance of Firmicutes in the guts of common cranes was higher than that in demoiselle cranes, and this may be related to the different feeding habits of the two cranes.…”
Section: Discussionmentioning
confidence: 99%
“…Diet is a significant contributor to fecal microbiota in a wide range of taxa, such as mammals (van Leeuwen et al., 2020 ; Zoelzer et al., 2021 ), birds (Schmiedová et al., 2022 ; Wang et al., 2022 ), fish (Härer & Rennison, 2023 ; Ringø et al., 2016 ), reptiles (Fong et al., 2020 ; Hoffbeck et al., 2023 ; Jiang et al., 2017 ), and amphibians (Chang et al., 2016 ; Wang, Smith, et al., 2021 ; Wang, Wang, et al., 2021 ). Diet can alter fecal microbiota in multiple ways.…”
Section: Discussionmentioning
confidence: 99%
“…Host taxonomy is frequently found to be the most significant impactor of virome composition [ 77 ], likely explained by viruses being obligatory intracellular parasites that depend on host factors such as specific cell receptor binding and replication machinery to infect and replicate within their host, and are therefore generally more host-specific. Contrastingly, non-viral microbiomes can be more generalised and are well documented as being more strongly influenced by non-host factors such as seasonality and geography [ 60 , 78 , 79 ], diet [ 80 , 81 ], age [ 82 ], and sex [ 78 , 83 ].…”
Section: Discussionmentioning
confidence: 99%